Lecturer’ and students’ perspectives on digital technology use in organizing and writing projects - Iskakova, Lyaila; Turikpenova, Sandugash; Abdykadyrova, Tursynai; Agranovich, Yelena; Karsybayeva, Raissa; Kultanov, Dastan (International Journal of Evaluation and Research in Education (IJERE), 2025)
This research aims to determine the problems experienced by lecturers and students in writing projects in order to determine the importance of technology in the organization of project activities. In this context, 24 students and 24 lecturers were included in the study. Six main themes were determined using a semi-structured interview form (general information, project preparation, project writing, cooperation and support, evaluation and feedback, result and presentation). It was concluded that 60% of the students and 20% of the faculty members had no previous experience in project writing. Lecturers and students (30%) had difficulty in finding a project title during the project preparation phase. A total 30% of the students did not know project writing, 50% of the lecturers had lack of knowledge and had problems in accessing the literature. Lecturers (70%) and students (60%) had no problems in finding a project team. Lecturers and students had some problems in sharing the project results, each project increased the knowledge skills of lecturers and students and created new project ideas. It is thought that training activities should be organized for lecturers and students on project writing and what kind of digital technologies they can benefit from in order to create new project ideas.